(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s
(3ChdgG (B:s
(3HeGOI bHh s
(3BNQgG (B:s
(3HHGH (B((3GdNeGSi ef GdcGa(B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B83 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B515s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3dZI (B10) s
Keywords: (3GddZIs